Engineering fluid flows and heat transfer analysis II - Laidoudi, Houssem; Makinde, Oluwole Daniel (Diffusion and defect data. Defect and diffusion forum ;, 2021)
Special topic volume with invited peer reviewed papers only. Engineering Fluid Flow and Heat Transfer Analysis II is a continuation of the previous volume 26 published in the journal of 'Diffusion Foundations'. This new volume issue of the journal 'Defect and Diffusion Forum' discusses results of the mathematical modeling and numerical investigation phenomena of heat transfer, mechanical agitation of various flow, natural and forced convection, fluid flow in the porous media, moving of magnetohydrodynamic flow and nanofluid. These results could be widely exploited in many engineering applications in the industry. Convection, Fluid Flow, Heat Transfer, Magnetohydrodynamic Flow, Mechanical Agitation, Micro Channel, Nanofluid, Numerical Modeling, Porous Media, Thermal Conductivity, Ventilation Materials Science, General Engineering, Mechanical Engineering.